2017
DOI: 10.1073/pnas.1617290114
|View full text |Cite|
|
Sign up to set email alerts
|

Protectin D1 n-3 DPA and resolvin D5 n-3 DPA are effectors of intestinal protection

Abstract: The resolution of inflammation is an active process orchestrated by specialized proresolving lipid mediators (SPM) that limit the host response within the affected tissue; failure of effective resolution may lead to tissue injury. Because persistence of inflammatory signals is a main feature of chronic inflammatory conditions, including inflammatory bowel diseases (IBDs), herein we investigate expression and functions of SPM in intestinal inflammation. Targeted liquid chromatography-tandem mass spectrometry-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 43 publications
3
105
0
Order By: Relevance
“…In the context of inflammatory bowel disease, systemic treatment with ω-3 DPA-derived protectin D1 and ω-3 DPAderived resolvin D5 protected against colitis and intestinal ischemia/reperfusion-induced inflammation in mice (101). In contrast, the inhibition of the activity of 15-lipoxygenase-one of the enzymes that mediates the synthesis of DPA-derived protectin D1-reduced the production of this anti-inflammatory SPM and, in turn, increased intestinal inflammation (101). These innovative strategies may be used to promote anti-inflammatory and tissue-protective effects in gut inflammatory disorders.…”
Section: Specialized Pro-resolving Lipid Mediators As Therapeutic Tarmentioning
confidence: 99%
“…In the context of inflammatory bowel disease, systemic treatment with ω-3 DPA-derived protectin D1 and ω-3 DPAderived resolvin D5 protected against colitis and intestinal ischemia/reperfusion-induced inflammation in mice (101). In contrast, the inhibition of the activity of 15-lipoxygenase-one of the enzymes that mediates the synthesis of DPA-derived protectin D1-reduced the production of this anti-inflammatory SPM and, in turn, increased intestinal inflammation (101). These innovative strategies may be used to promote anti-inflammatory and tissue-protective effects in gut inflammatory disorders.…”
Section: Specialized Pro-resolving Lipid Mediators As Therapeutic Tarmentioning
confidence: 99%
“…BLT1 is abundantly expressed by polymorphonuclear neutrophils (PMNs), whereas ChemR23 is expressed by macrophages and dendritic cells, although it can also be expressed by VSMCs and platelets (15,16). Notably, RvE1 has been shown to possess protective properties in a number of inflammatory-disease animal models, including peritonitis (8), colitis (17), polymicrobial sepsis (18,19), airway inflammation (20)(21)(22), acute kidney injury (23), asthma (22), and myocardial infarction (24). Previous studies have also demonstrated that fish oil intake (mainly containing EPA and docosahexaenoic acid) can suppress balloon injury-induced arterial neointima formation in animals (25).…”
mentioning
confidence: 99%
“…Given the role that omega‐3 fatty acid‐derived specialized pro‐resolving mediators play in the resolution of colonic inflammation, we next investigated whether FSO, AO, and FO regulated the concentrations of these molecules during colonic inflammation. In colon samples, we identified mediators from all four major fatty acid metabolomes in accordance with published criteria . Using Partial Least Square Discriminant Analysis, which generates a regression model based on concentrations of lipid mediators that are differently expressed between two groups, we found that each of the three supplement groups gave a distinct lipid cluster from mice given SO ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%